The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.seppur.2017.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical synthesis, characterization and photodegradation of organic pollutant over Nd2O3 nanostructures prepared via a new simple route

Abstract: For the first time, a new simple route of synthesizing Nd 2 O 3 nanostructures has been developed with applying the sonochemical process. As a novel precipitator, 2,2-dimethyl-1,3-propanediamine was applied in the presence of Nd(NO 3) 3 .6H 2 O to prepare neodymium oxide. In order to control the shape, size and photocatalytic activity of neodymium oxide products, the type of capping agents have been altered. The synthesized nanostructured neodymium oxide has been characterized with the aid of DRS, FT-IR, XRD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The size and morphology of samples were determined using field‐emission scanning electron microscopy (FESEM). Our previous studies showed that shape and size of nanomaterials could be influenced by various capping agents . Figure shows the as‐synthesized pure nickel ferrite using different capping agents such as PVP, fructose, glucose, and maltose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size and morphology of samples were determined using field‐emission scanning electron microscopy (FESEM). Our previous studies showed that shape and size of nanomaterials could be influenced by various capping agents . Figure shows the as‐synthesized pure nickel ferrite using different capping agents such as PVP, fructose, glucose, and maltose.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that shape and size of nanomaterials could be influenced by various capping agents. [39,40] Figure 3 shows the as-synthesized pure nickel ferrite using different capping agents such as PVP, fructose, glucose, and maltose. As seen in Figure 3a, aggregated structures, large size, and heterogeneous particles are characteristic of structures that are synthesized using PVP (sample 1).…”
Section: Characterization Of the Magnetic Nanocatalystmentioning
confidence: 99%
“…To date, a variety of approaches for making the nanostructured Re 2 Zr 2 O 7 has been offered and employed like combination of the sol–gel and co-precipitation [13] , floating zone technique [14] , solid-state reaction [6] , [15] , microwave plasma technique [16] and Pechini approach [17] . Use of ultrasonic approach for making the nanoscale compounds, has fascinated extraordinary attention for its ease, fastness and low cost as well as its environmental friendliness [18] , [19] , [20] , [21] . Thus, many scientists have been tried to create a variety of nano compounds with the help of ultrasonic path [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…As well as, many attempts have been put on the shape and sizecontrolled preparation of nanostructures [12][13][14][15]. Besides, most of such mesoporous drug storage/release systems are silica based materials such as MCM-41, SBA-15, etc.…”
Section: Introductionmentioning
confidence: 99%